How Students Use Statistical Computing in Problem Solving. (9th December 2020) - Woodard, Victoria; Lee, Hollylynne
Abstract: As the demand for skilled data scientists has grown, university level statistics and data science courses have become more rigorous in training students to understand and utilize the tools that their future careers will likely require. However, the mechanisms to assess students' use of these tools while they are learning to use them are not well defined. As such, a framework to assess statistical computing actions was created. Using task-based interviews of students who completed a second course in statistics, the framework was used to determine the ways in which students utilize statistical computing tools, specifically R, while going through problem solving phases. Patterns that emerged are discussed. Supplementary materials for this article are available online.